Competition in Business: Analysis of Factors Affecting Customers Switching Intention of Conventional Banks to Islamic Banks in Central Java - Firdiyanti, Shovia Indah; Abdillah, Mujiyono; Prasetyoningrum, Ari Kristin; Fuadi, Nasrul F. Z (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study uses a combination of two theories, namely Theory Reasoned Action (TRA) and Theory Push-Pull-Mooring (PPM). This study aims to determine the effect of religious attitude, alternative attractiveness and subjective norm on customers switching intention. The research method used is quantitative. This study uses primary data distributed to respondents with purposive sampling technique. The population in this study are Islamic bank customers who have previously been customers of conventional banks in Central Java who are Muslim. The sample used is 100 respondents obtained through distributing questionnaires. This research uses multiple regression analysis technique with Smart-PLS software. The results of hypothesis testing indicate that religious attitude, alternative attractiveness and subjective norm have a positive and significant effect on customers switching intentions on Islamic bank customers. The result of the highest influence is shown by the subjective norm variable with a regression coefficient value of 0,375 with a significance value of 0,000. This means that a person's intention to perform a behavior can be built through their social environment. The greater the support from the social environment such as family, friends, neighbors and religious leaders can influence the intention of conventional customers to immediately switch to Islamic bank.